THIRD PARTY LOGISTICS REDUCES COST, MYTH OR REALITY? CASE STUDY OF THE RETAIL INDUSTRY OF MAURITIUS - Persand, Luvkishan; Pertaub, Sachi; Seenarain, Ashvin (PEOPLE: International Journal of Social Sciences, 2018)
This study looks at various perspectives about third party logistics and the advantages and disadvantages when outsourcing to 3pl. It also discusses the various risks that are related to third party logistics. The main objectives were to find out on how the various benefits and drawbacks that are related to outsourcing to a third party logistics (3PL). Another aim is to verify the impact of using 3PL in Mauritius. One of the objectives was to find on the benefits related to 3PL. Another aim was to find out on the drawbacks related to 3PL. The methodology used for this study was questionnaire survey quantitative methods among 135 respondents who were from different cooperative sector but response rate was 120. This questionnaire investigates the various advantages, disadvantages and risks related to third party logistics. After this process, data collected has been analyzed using SPSS 22.0 where demographics analysis, cross tabulation and t-test analysis was performed to find the relationship between the variables. The findings demonstrate that outsourcing of 3PL is slowly becoming famous among suppliers.